2021
DOI: 10.1016/j.heliyon.2021.e06404
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of corporate image in the hospitality industry East Java, Indonesia

Abstract: The purpose of this study is to determine how the perceptions and understandings of hotel managers in East Java to improve the corporate image as a hotel marketing strategy. Research respondents are managers who work in the hospitality industry. A total of ninety-six stars hotel in East Java were assessed. Each star hotel has nine managers so that the study population is 621 managers. The research sample of 232 managers. The sampling technique is simple random sampling. Statistical techniques used Confirmatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Furthermore, the results of this study showed a positive and significant relationship between corporate image and customer trust. A study by Triatmanto et al [60] revealed how the experiences and beliefs of hotel management in East Java enhance the corporate image as a marketing strategy of a hotel. Managers of the hospitality industry were selected as research respondents for this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the results of this study showed a positive and significant relationship between corporate image and customer trust. A study by Triatmanto et al [60] revealed how the experiences and beliefs of hotel management in East Java enhance the corporate image as a marketing strategy of a hotel. Managers of the hospitality industry were selected as research respondents for this study.…”
Section: Discussionmentioning
confidence: 99%
“…The hotel industry's psychological image can be described by several methods, comprising trust, favorability, status, and recognition. Corresponding to the opinion of the hotel managers the corporate image is exhibited by the customers' trust in the hotel [60]. It is also found that the hotel management finds trust to be a major factor for attracting visitors to the hotel.…”
Section: Customer Trust and Corporate Imagementioning
confidence: 95%
See 3 more Smart Citations